Internet of things solar irrigation system - Afyq Rukaini, Mohd Ruzaini (2021)
This thesis discusses the advancement of Internet of Things (IoT)-enabled portable solar irrigation systems. The major goal of this project is to be able to monitor and manage the waterpump through wifi while also receiving power from the solar panel. Furthermore, the water pump may increase the flow rate and pressure of the water. Many Power Generation or Power Plants, for example, use natural gas to create energy. As a result, in order to lessen our dependency on natural gas, we may tum to other energy sources such as solar energy. Furthermore, this alternative energy has no negative environmental consequences. Human labour is often used in the irrigation system. As a result, labour and employee wages are exorbitantly high. Water is a significant priority for users. Water is utilised for many things, including drinks, bathing, and washing. Aside from that, water is essential for watering plants because it may nourish them. However, many people's irrigation equipment is inefficient. This is because irrigation now relies on human effort. The water pump may filter the reservoir's water into clean water that humans can drink on a regular basis.